Epigenetic Regulation of Key Enzymes CYP7a1 and HMGCR Affect Hepatic Cholesterol Metabolism in Different Breeds of Piglets - Li, Xian; Xiao, Hanyang; Jian, Xiaoqian; Zhang, Xiangyin; Zhang, Hui; Mu, Yang; Wang, Hua; Chen, Shulin; Cong, Rihua (Frontiers in Veterinary Science, 2020)
Liver is the place where cholesterol is synthesized, transported, secreted and transformed, thus liver takes an irreplaceable role in cholesterol homeostasis. Hepatic cholesterol metabolism differs between breeds, yet the molecular mechanism is unclear. In this study Large White(LW) and Erhualian(EHL) piglets (at birth and 25-day-old) were used, 6 each time point per breed. Erhualian piglets had significantly lower body and liver weight compared with Large White at birth and weaning, but the liver/ body weight ratio was higher at weaning, associated with increased serum and liver cholesterol and triglyceride content. The mRNA expression of Cholesterol-7alpha-hydroxylase (CYP7α1) and Recombinant Acetyl Coenzyme Acetyltransferase 2(ACAT2) were down-regulated in Erhualian piglets at birth, while hepatic Sterol-regulatory element binding protein 2(SREBP2) mRNA expression was up-regulated in Erhualian piglets at weaning, as well as SREBP2 protein content, compared with Large White piglets. At birth, the depressed CYP7α1 transcription in Erhualian piglets was associated with decreased Histone H3 (H3) and increased Histone H3 lysine 27 trimethylation(H3K27me3). While the results revealed significant promoter hypermethylation of 3-Hydroxy-3-methylglutaryl-CoA reductase (HMGCR) promoter in Erhualian piglets at weaning, together with increased Histone H3 lysine 9 monomethylation (H3K9me) and Histone H3 lysine 4 trimethylation (H3K4me3). These results suggest that epigenetic modification may be an important mechanism in hepatic cholesterol metabolism among different species, which is vital for maintaining cholesterol homeostasis and decreasing risk of cardiovascular disease.